2009
DOI: 10.4049/jimmunol.0800448
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Repertoire of ASC-Mediated Gene Expression

Abstract: Apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) is an adaptor molecule that mediates inflammatory and apoptotic signals. Although the role of ASC in caspase-1-mediated IL-1β and IL-18 maturation is well known, ASC also induces NF-κB activation and cytokine gene expression in human cells. In this study, we investigated the molecular mechanism and repertoire of ASC-induced gene expression in human cells. We found that the specific activation of ASC induced AP-1 activity, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…36 An ASC/caspase-8-dependent pathway has been described in immortalised cell lines 37 not expressing caspase-1. 38 We have detected both ASC and caspase-1 in CD4 and CD8 T cells as well as in B cells (data not shown) indicating that caspase-1 expression is not restricted to myeloid cells. At this time, we do not know if such cells exist in a physiological context.…”
Section: Aim2/asc-dependent Caspase-8-mediated Apoptosis R Pierini Ementioning
confidence: 92%
“…36 An ASC/caspase-8-dependent pathway has been described in immortalised cell lines 37 not expressing caspase-1. 38 We have detected both ASC and caspase-1 in CD4 and CD8 T cells as well as in B cells (data not shown) indicating that caspase-1 expression is not restricted to myeloid cells. At this time, we do not know if such cells exist in a physiological context.…”
Section: Aim2/asc-dependent Caspase-8-mediated Apoptosis R Pierini Ementioning
confidence: 92%
“…Whereas ASC may mediate effects on adipocyte hypertrophy, as observed in Casp-1 −/− animals, macrophage influx in the ASC −/− animals may partly be regulated independently of caspase-1. In this regard, recent studies reported that ASC directly mediates gene expression (28) and has a critical role in the development of experimental autoimmune encephalomyelitis and arthritis independently of the inflammasome (29, 30). However, in obesity, several of the parameters tested suggest that ASC and caspase-1 work in the same pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that a connection between ASC and the transcription factor AP1 has recently been established using a reconstituted cell system that is engineered to respond to the bacterial cell wall component muramyl dipeptide (25). AP1 is among a large number of transcriptional regulators that are downstream targets of MAPKs (26).…”
Section: Discussionmentioning
confidence: 99%
“…ASC has been proposed to regulate cytokine transcription through activation of NF-B (23,24). AP1, STAT3, ISGF3, and NF-AT have also been identified as transcriptional ASC targets in a reconstituted cell system with exogenously expressed ASC and a chimeric CARD12/NOD2 protein (25). Given the complexity of inflammatory signaling, it is likely that additional signaling pathways contribute to inflammasome-independent ASC function in macrophages.…”
mentioning
confidence: 99%